Tingkat Kecemasan Orang Tua Yang Memiliki Anak Berkebutuhan Dalam Menghadapi Kesiapan Masuk Sekolah Dasar - Alurmei, Wahyu Aulizalsini; Pohan, Hema Dayita; Azzahra, Salsabila Putri; Dewi, Vanesa Kusuma (Peneliti.net, 2024)
This study aims to assess the level of anxiety among parents regarding the readiness of children with special needs (CWSN) for entering elementary school. Using a descriptive quantitative research method, the study involved 37 parents of CWSN, employing questionnaires as the data collection technique. Statistical analysis revealed that all samples (100%) experienced a high level of anxiety. The results also indicated that this high anxiety level is related to parental concerns about their children's academic and social abilities in the elementary school environment. The study found that parental anxiety can negatively impact their emotional well-being and may affect the child’s development. The primary recommendation is to provide informational support and training for parents to reduce anxiety and enhance the readiness of CWSN for primary education.